Efektivitas Penggunaan Media Audiovisual terhadap Keterampilan Menulis Teks Eksposisi Siswa SMP - Puspita, Dela; Septyanti, Elvrin; Permatasari, Silvia (GERAM: Gerakan Aktif Menulis, 2023)
Learning media is a tool to optimize the delivery of material in learning. The aim is so that students do not get bored and lose focus when the teacher delivers material if they only use print media. One of them is audiovisual media which contains images and sound (video). Therefore, researchers are interested in conducting research with the title, "Effectiveness of Using Audiovisual Media on Expository Text Writing Skills for Class VIII Middle School Students". This research aims to determine the level of effectiveness of using audiovisual learning media on the expository text writing skills of class VIII students at SMP Muhammadiyah 1 Pekanbaru. The type of research carried out by researchers is experimental research with a quantitative approach. Data collection methods are observation and skills tests. Data analysis techniques are normality test, homogeneity test, and paired t-test. After calculating after treatment the average obtained in the control class was 79 in the medium category, while the experimental class was 85 in the high category, which means the results increased. From the results of the paired t-test, a significant value (2-tailed) of 0.00 < 0.05 was obtained, meaning that H0 was rejected and H1 was accepted, meaning that there were influences and differences in the application of the use of audiovisual media on students' ability to write expository texts. The criteria for rejecting H0 can also be seen from the value Thit > Ttab, namely 2.90 > 1.60.